OsbZIP47 Is an Integrator for Meristem Regulators During Rice Plant Growth and Development - Prakash, Sandhan; Rai, Rashmi; Zamzam, Mohamed; Ahmad, Owais; Peesapati, Raghavaram; Vijayraghavan, Usha (Frontiers in Plant Science, 2022)
Stem cell homeostasis by the WUSCHEL–CLAVATA (WUS-CLV) feedback loop is generally conserved across species; however, its links with other meristem regulators can be species-specific, rice being an example. We characterized the role of rice OsbZIP47 in vegetative and reproductive development. The knockdown (KD) transgenics showed meristem size abnormality and defects in developmental progression. The size of the shoot apical meristem (SAM) in 25-day OsbZIP47KD plants was increased as compared to the wild-type (WT). Inflorescence of KD plants showed reduced rachis length, number of primary branches, and spikelets. Florets had defects in the second and third whorl organs and increased organ number. OsbZIP47KD SAM and panicles had abnormal expression for CLAVATA peptide-like signaling genes, such as FON2-LIKE CLE PROTEIN1 (FCP1), FLORAL ORGAN NUMBER 2 (FON2), and hormone pathway genes, such as cytokinin (CK) ISOPENTEYLTRANSFERASE1 (OsIPT1), ISOPENTEYLTRANSFERASE 8 (OsIPT8), auxin biosynthesis OsYUCCA6, OsYUCCA7 and gibberellic acid (GA) biosynthesis genes, such as GRAIN NUMBER PER PANICLE1 (GNP1/OsGA20OX1) and SHORTENED BASAL INTERNODE (SBI/OsGA2ox4). The effects on ABBERANT PANICLE ORGANIZATION1 (APO1), OsMADS16, and DROOPING LEAF (DL) relate to the second and third whorl floret phenotypes in OsbZIP47KD. Protein interaction assays showed OsbZIP47 partnerships with RICE HOMEOBOX1 (OSH1), RICE FLORICULA/LEAFY (RFL), and OsMADS1 transcription factors. The meta-analysis of KD panicle transcriptomes in OsbZIP47KD, OsMADS1KD, and RFLKD transgenics, combined with global OSH1 binding sites divulge potential targets coregulated by OsbZIP47, OsMADS1, OSH1, and RFL. Further, we demonstrate that OsbZIP47 redox status affects its DNA binding affinity to a cis element in FCP1, a target locus. Taken together, we provide insights on OsbZIP47 roles in SAM development, inflorescence branching, and floret development.